Strategi Cyber Public Relations dalam Pembentukan Citra Institusi Pendidikan Tinggi Swasta - E. B., Gita Aprinta (Universitas Semarang, 2014)
As a strategy public relations, cyber public relations gives the new meaning for public relations practioners, especially in buliding positive image of private university (PTS). Trough cyber public relations, communcation between PTS and it public, can be bridge quickly and easy. Moreover, cyber public relations strategy provides dynamic and personal interaction, so that public posses their personal intepretation about the PTS.